2008
DOI: 10.1016/j.neuroscience.2008.02.060
|View full text |Cite
|
Sign up to set email alerts
|

Stoned B mediates sorting of integral synaptic vesicle proteins

Abstract: A continuous supply of fusion-competent synaptic vesicles is essential for sustainable neurotransmission. Drosophila mutations of the dicistronic stoned locus disrupt normal vesicle cycling and cause functional deficits in synaptic transmission. Although both Stoned A and B proteins putatively participate in reconstituting synaptic vesicles, their precise function is still unclear. Here we investigate the effects of progressive depletion of Stoned B (STNB) on the release properties of neuromuscular synapses us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 52 publications
4
18
0
Order By: Relevance
“…This work has revealed that several functional characteristics of adult neuromuscular synapses are distinct from those that we and others described previously in the larva (Fig. S8) (50,51). In the present study, comparison of glutamatergic DLM neuromuscular synapses and cerebellar CF-PC synapses revealed a surprising degree of conservation in the detailed properties of synaptic function.…”
Section: In Vivo Function For Nsf In Maintaining Active Zone T-snaressupporting
confidence: 54%
“…This work has revealed that several functional characteristics of adult neuromuscular synapses are distinct from those that we and others described previously in the larva (Fig. S8) (50,51). In the present study, comparison of glutamatergic DLM neuromuscular synapses and cerebellar CF-PC synapses revealed a surprising degree of conservation in the detailed properties of synaptic function.…”
Section: In Vivo Function For Nsf In Maintaining Active Zone T-snaressupporting
confidence: 54%
“…S2). Synaptic vesicle density at the active zone (<250 nm from T-bar; Rohrbough et al, 2007) and in the reserve domain (250-500 nm from T-bar; Mohrmann et al, 2008) was elevated in mmp2 single mutants, with a similar nonsignificant trend in mmp1 mutants (Fig. 3A,B).…”
Section: Mmp1 and Mmp2 Both Regulate Differentiation Of Synapse Functionmentioning
confidence: 76%
“…Alternatively, the increase in mEPSC frequency may be a consequence of the reduction in dendritic lengths, allowing more dendrites to be spared during the slice preparation procedure. MMP-9 can also directly regulate neurotransmitter release through proteolysis of critical effectors (Mohrmann et al , 2008; Varley et al , 2011). For example, MMP-9-dependent proteolysis of neuroligin 1 (NLG1), a postsynaptic adhesion molecule at glutamatergic synapses, destabilizes presynaptic neurexin-1β and reduces mEPSC frequency (Peixoto et al , 2012).…”
Section: Discussionmentioning
confidence: 99%